READING STRATEGIES AS DEVELOPMENT MODEL ENGLISH COGNITION OF SENIOR HIGH SCHOOL STUDENTS - S Supeno; imam suseno; Lubban Anwari Alhamidi (IJEE (Indonesian Journal of English Education), 2017)
ABSTRACT This study aims to develop a model of reading strategies of English language learning which is expected to further enhance students’ cognitive abilities in English. The model reading strategies serve as a strategy to read the English subtitles via bottom-up, top-down and mixed strategies that are capable of triggering the students' critical thinking and have been integrated with development ideas from experts and linguists. The study employed a cluster random sampling of 30 schools and 900 students for the standardization of the model reading strategies as a new model that best enhance the cognitive power of English language learning. The method used was Research and Development, through  seven steps in the research cycles. The subjects were high school students in the class tenth in  Special Capital Region of Jakarta. The steps to reading development strategy that are able to improve the cognitive of students are 6 steps consisting of:  overall understanding,  understanding on contextual meaning,  assumption of contextual meaning,  look for meaning in contextual output,  searching for further meaning, and  returning to the main idea of ​​our thinking.   ABSTRAK Penelitian ini bertujuan mengembangkan model pembelajaran bahasa Inggris yakni reading strategies, yang diharapkan dapat meningkatkan daya kognitif bahasa Inggris siswa. Permodelan reading strategies sebagai strategi untuk membaca teks bahasa Inggris melalui strategi bottom-up, top-down dan mixed yang mampu memicu pemikiran kritis siswa dan telah diintegrasikan dengan gagasan pengembangan dari para ahli dan ahli bahasa. Dengan cluster random sampling terpilih sebanyak 30 sekolah dan 900 siswa untuk standarisasi model reading strategies sebagai model baru yang dapat meningkatkan daya kognitif bahasa Inggris siswa. Metode yang digunakan adalah Research and Development, melalui tujuh langkah dalam siklus penelitian. Subjek penelitian adalah siswa SMA di kelas sepuluh di DKI Jakarta. Hasil penelitian menunjukkan bahwa reading strategies yang dapat meningkatkan kemampuan kognitif siswa yaitu melalui adalah 6 langkah strategi membaca yaitu:  pemahaman teks secara utuh, memahami makna dalam konteks, berpikir dan menduga tentang makna, mencari makna dalam konteks, mencari makna lebih jauh, dan kembali pada pemikiran makna kata. How to Cite: Supeno. Suseno,I. Alhamidi, L. A. (2017). Reading Strategies as Development Model English Cognition of Senior High School Students. IJEE (Indonesian Journal of English Education), 4(1), 84-96, doi:10.15408/ijee.v4i1.4822DOI: http://dx.doi.org/10.15408/ijee.v4i1.4822